Effect of Intellectual Capital, Corporate Sustainability Disclosure, and Corporate Governance To The Value of The Company: Empirical Study on Registered SOE in Indonesia Stock Exchange - Ronald Tauviek Andi Kasim; Djokosantoso Moeljono; Jangkung Handoyo Mulyo (Jurnal Ilmu Manajemen & Ekonomika, 2018)
The main purpose of the company’s operation today is to maximize the value of the company. Corporate value is not only influenced by economic performance, but can come from performance derived from social activities. But in reality, it eventually leads to a conflict of interest that occurs within the company, so that necessary to implement mechanisms to reduce the conflict. The purpose of this research to provide evidence to determine effect of intellectual capital, corporate sustainability disclosure, and corporate governance to corporate values with company size and leverage as control variables. This research can provide benefits as knowledge related to how wide the company pursues intellectual capital, corporate social responsibility, and corporate governance in increasing the value of the company. This research samples is focused on state owned enterprises listed in Indonesia Stock Exchange for period 2013 – 2016 with total 48 data used in this research. This research use multiple regression to test the hypothesis. The result of this research is intellectual capital and corporate sustainability disclosure have positively influence towards corporate values. Corporate governance has no influence towards corporate values. For control variables, company size has no influence towards corporate values and leverage has negatively influence towards corporate values.